Paleography and Graphoscopy: the relevance of pallographic transcription and grafotechnic analysis as instruments of access to information - Ribeiro, Alexandre Edmundo Eltermann (2017)
The present paper aims to present Paleography as a science that interprets the manuscripts, allowing the original idea of the document not to be lost. In addition to identifying the Grafoscopia as a tool to identify individual characteristics of the writing of each person. In order to do so, it was used as study the minutes of installation and first hearing of the Conciliation and Trial Boards of the Municipality of Florianópolis, dated June 5, 1934. In the paleographic transcription, the contents acquired in the field of Paleography were used as base, comprising a brief history, description of technical standards used, and the presentation of abbreviations, acronyms, expressions and greetings that may cause doubts when transcribing a manuscript. In Grafoscopia, the analysis was based on the investigation of the habits characteristic of the writing of the author of the minutes, addressing the morphological aspects, of pressure, axial inclination, among other peculiarities of an authentic tracing. Finally, there was the interconnection between Archivology, Paleography and Grafoscopy.